Nonlinear associations of depression and sleep duration with cognitive impairment in older adults with hypertension: findings from a national survey - Hui-Ying Fan; Hui-Ying Fan; Hui-Ying Fan; He-Li Sun; He-Li Sun; Yuan Feng; Qinge Zhang; Hua-Qing Xing; Hua-Qing Xing; Qian-Hua Huang; Qian-Hua Huang; Zhaohui Su; et al. (Frontiers in Aging Neuroscience, 2025)
ObjectivesCognitive impairment is a major health concern in older adults with hypertension, and both depression and abnormal sleep duration are recognized as potential contributing factors. This study aimed to explore the nonlinear association of depression and sleep duration with cognitive impairment among older adults with hypertension.MethodsThis cross-sectional study was based on the 2017–2018 wave of Chinese Longitudinal Healthy Longevity Survey. Depression and cognitive function were measured using the 10-item Center for Epidemiological Studies Short Depression Scale and Mini Mental State Examination, respectively. Univariate, binary logistic regression, and restricted cubic spline regression analyses were used to examine the associations between depression, sleep duration and cognitive impairment.ResultsA total of 3,989 older adults with hypertension were included. The prevalence of depression and cognitive impairment were 28.1% (95%CI = 26.7–29.5%) and 10.1% (95%CI = 9.2–11.1%), respectively. After adjusting for confounding factors, a significant linear association (nonlinear p = 0.814) between depression and cognitive impairment risk was found, while a U-shaped nonlinear association was identified between sleep duration and cognitive impairment risk (p = 0.040). Both shorter (<6.6 h) and longer (>7.7 h) sleep duration per day were associated with higher cognitive impairment risk, with an inflection point at 7.3 h. The effect of sleep duration on cognitive impairment risk was more significant for participants with a higher (≥ 6 years) education level.ConclusionThis study highlights the importance of managing depression and optimizing sleep duration in addressing the risk of cognitive decline in older adults with hypertension.